The Asymmetric Effect of Bankruptcy Fraud in Sweden: A Long-Term Perspective - Box, Marcus (Journal of quantitative criminology, 2019)
The knowledge of the effects of white-collar crimes is incomplete. In the article, we operationalize white-collar crimes as bankruptcy frauds. Economic models maintain that interlinkages between firms may give ‘domino effects': bankruptcy events could lead to ‘bankruptcy chains' in which a bankruptcy spreads to other firms. Analogously, criminologists assert that social and economic networks can be a major source of fraud diffusion, with the potential to drive other firms bankrupt. Recent empirical results show that crimes may have detrimental and even asymmetric (nonlinear) effects on economic activity. We analyze the diffusion and the aggregate development of bankruptcy frauds in Sweden over nearly two hundred years, specifically focusing on the relationship between bankruptcy frauds and the bankruptcy volume. We also consider linkages between bankruptcy frauds, bankruptcies, and the macroeconomic cycle.